(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
This article explores the transformative role of pedagogical technologies in enhancing the knowledge, skills, and qualifications of students, with a specific emphasis on the innovative Ahmadiyya approach. The article provides insights into the methods, results, and implications of using Ahmadiyya pedagogical technologies and their potential to revolutionize modern education